Oxidative and nitrative stress-related changes in human lens epithelial cells following exposure to X-rays. (7th March 2018) - Bahia, Simran; Blais, Erica; Murugkar, Sangeeta; Chauhan, Vinita; Kumarathasan, Premkumari
Abstract: Purpose: There is limited understanding of the mechanistic effects of ionizing radiation (IR) exposure in cataract formation. In this study, we explored the effects of IR on reactive oxygen/nitrogen species (ROS and RNS) generation in human lens epithelial (HLE) cells as an early key event to long-term damage. Materials and methods: HLE cell-line was exposed to X-rays at varied doses (0–5 Gy) and dose-rates. Cell lysates and supernatants were collected 20 h post-exposure and analysed for viability, cell cycling and metabolites of ROS (p, m-, o-, tyrosines, 3-chlorotyrosine (cl-tyrosine), 8-hydroxy deoxyguanosine, (8-OH-dG) and RNS (3-nitrotyrosine). Results and conclusions: HLE cell-line exhibited a bi-phasic response in terms of cell viability, ROS and RNS profiles. At doses <0.5 Gy, ROS and RNS levels were lower than control and at higher doses (>0.5 Gy) a steady increase was observed in each metabolite. This response was observed irrespective of dose-rate. Among the associations tested, cl, p, m-tyrosine and 3-nitrotyrosine revealed changes ( p  < .05) at 5 Gy compared exclusively to 0.05 and 0.01 Gy. In addition, dose-rate related differences were observed. Overall, the data suggests that ROS and RNS are key events in radiation induced damage and this response is dependent on the dose and dose-rate of IR exposure.